Механізм впровадження військового податку в Україні: досвід періоду Першої та Другої світових війн і сучасність - Орлик, С. В.; Orlyk, S. (КНТУ, 2015)
У статті розглянуто проблеми впровадження військового податку в Україні в часи Першої та Другої світових війн, а також у зв’язку з війною на Сході України (АТО). Визначено причини та наслідки впровадження військового податку з фізичних осіб. Досліджено податковий механізм справляння військового податку з фізичних осіб у різні періоди. Розглянуто повноваження та функції органів, на які покладалося адміністрування військового податку. Проведено історичні аналогії з нині діючим механізмом стягнення військового збору в Україні.The article deals with the problem of introducing the military tax in Ukraine during the World War I and World War II, as well as the war in the East of Ukraine (ATO). The reasons and arguments of introducing the military tax to individuals are specified. The military tax collection mechanism from individuals in different historical periods is studied. We consider the powers and functions of the bodies that were to manage the military tax. A historical analogy with the existing mechanism of collecting military tax in Ukraine was carried out, which showed that while introducing the military taxes in terms of two world wars and the current war in the East of Ukraine (ATO), the efficiency and low cost have always been the main terms of its introduction etc.
The Mechanism of Introducing the Military Tax in Ukraine: the Experience of the World War I and World War II and Modern Times
Keywords: військовий податок; Перша світова війна; Друга світова війна; Україна; Російська імперія; оподаткування; податкова політика; податний інспектор; війна на Сході України (АТО); military tax; World War I; World War II; Ukraine; Russian Empire; taxation; tax policy; tax-paying inspector; the war in the East of Ukraine; ATO